2020
DOI: 10.1017/s1047951120003923
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of adults with congenital heart disease that experience acute kidney injury in the intensive care unit

Abstract: Background: Young adults with congenital heart disease (CHD) are increasing in number with an increased risk for acute kidney injury. Little is known concerning the impact of non-recovery of kidney function for these patients. Therefore, we sought to explore the rates of acute kidney disease, persistent renal dysfunction, and their associations with adverse outcomes in young adults with CHD. Methods: This is a single-centre retrospective study including all patients at the ages of 18–40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…We identified patient (eg, comorbidities) and CKRT (eg, time to initiation and liberation pattern) characteristics associated with adverse kidney outcomes 90 days after CKRT initiation. It is known that AKI is common in patients with congenital heart disease and is associated with their morbidity and mortality . In this study, we found the highest odds of MAKE-90 outcomes in patients with cardiac comorbidities.…”
Section: Discussionsupporting
confidence: 49%
“…We identified patient (eg, comorbidities) and CKRT (eg, time to initiation and liberation pattern) characteristics associated with adverse kidney outcomes 90 days after CKRT initiation. It is known that AKI is common in patients with congenital heart disease and is associated with their morbidity and mortality . In this study, we found the highest odds of MAKE-90 outcomes in patients with cardiac comorbidities.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, the authors reported that all patients who died within the first year after hospital discharge had CKD. (Fuhrman et al, 2021) Another study by Kwiatkowski et al reported a 36% incidence of AKI among ACHD patients undergoing cardiac surgery. Significant risk factors for AKI were older age (≥35), underlying left ventricular dysfunction or arrhythmia, longer cardiopulmonary bypass time, and perioperative vancomycin use.…”
Section: Surgery Nephrotoxin Exposure and Kidney Complicationsmentioning
confidence: 99%
“…Recently, KDIGO published an updated definition of AKD in an effort to combine prior definitions and improve future research efforts 7 . Study results have shown that adult patients with cirrhosis, 8 congenital heart disease, 9 and after cardiac procedures 10 meeting criteria for AKD, with or without AKI, have an increased risk of poor outcomes such as progression to CKD and mortality. Currently, there are no studies in pediatric non‐kidney solid organ transplant patients specifically exploring the progression of kidney disease as defined by AKI, AKD, and CKD using the most current definitions.…”
Section: Introductionmentioning
confidence: 99%